A Study of Clinico-Histopathological Correlation of Leprosy in A Tertiary Care Hospital, KIMS, Hubballi, Karnataka - N, Sindhushree; Vernekar, Sunita S (Annals of Pathology and Laboratory Medicine, 2019)
Background: Leprosy is a chronic infectious disease affecting mainly cutaneous and peripheral nervous system. Histopathology provides confirmatory information for suspected cases which can be missed in clinical practice or epidemiological studies and helps in exact typing. This study was conducted to know the correlation between clinical and histopathological diagnosis of Leprosy. Methods: This was both a retrospective study and prospective study, undertaken in the Department of Pathology, Karnataka Institute of Medical Sciences, Hubballi, over a period of 42 months from January 2013 to June 2016. Punch biopsies were taken from clinically diagnosed, clinically suspected cases of leprosy, relapse cases and lepra reactions and histopathological examinations were carried upon. Results: A total of 280 patients were studied. Of them 193 patients (68.92%) were males and rest 87 (31.08%) patients were females. The maximum incidence was seen in the age group of 21-40yrs with 127cases (45.36%). Maximum number of patient both clinically and histologically belonged to Borderline tuberculoid leprosy. Clinical and histopathological correlation was seen in 61 cases (33.70%). Conclusion: Correlation of clinical and histopathological features along with bacteriological index is more useful for accurate typing of leprosy than considering single parameter alone.